2021
DOI: 10.3390/polym13213736
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Lignocellulolytic Enzyme Activities in Fungal Species and Sequential Solid-State and Submerged Cultivation for the Production of Enzyme Cocktails

Abstract: Various fungal species can degrade lignocellulolytic materials with their enzyme cocktails composed of cellulolytic and lignolytic enzymes. In this work, seven fungal species (Mucor indicus DSM 2185, Paecilomyces variotii CBS 372.70, Myceliophthora thermophila CBS 663.74, Thielavia terrestris CBS 456.75, Botryosphaeria dothidea JCM 2738, Fusarium oxysporum f.sp. langenariae JCM 9293, and Fusarium verticillioides JCM 23107) and four nutrient media were used in the screening for effective lignocellulose degradin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“…Other studies also reported cellulose degradation when treating the biomass with T. versicolor , leading to significant decreases in SCOA production [ 63 , 64 ]. This could justify the low SCOA production of PvSSF, since P. variotii is known to have high cellulosic and hemicellulosic activities [ 65 ].…”
Section: Resultsmentioning
confidence: 99%
“…Other studies also reported cellulose degradation when treating the biomass with T. versicolor , leading to significant decreases in SCOA production [ 63 , 64 ]. This could justify the low SCOA production of PvSSF, since P. variotii is known to have high cellulosic and hemicellulosic activities [ 65 ].…”
Section: Resultsmentioning
confidence: 99%
“…In order to obtain an efficient cocktail, some parameters must be taken into account, such as microorganisms’ behavior when cultivated on different substrates, identifying the types of enzymes they produce in each case, and which enzymes are necessary for every kind of substrate degradation [ 60 ]. Various approaches can be used for enzymatic cocktails production, such as combinations of distinct species of fungi [ 248 , 249 , 250 , 251 ], bacteria [ 252 , 253 , 254 ], or even fungi and bacteria [ 255 , 256 , 257 ]. Furthermore, strategies for optimizing an enzymatic cocktail may include supplementation with a specific enzyme, be it hydrolytic or not, or supplementation with surfactants or other chemicals [ 247 ].…”
Section: Lignocellulolytic Enzymes Productionmentioning
confidence: 99%
“…Several studies have already shown the efficiency of bioprospecting in searching for lignocellulolytic microorganisms aiming at producing enzymatic cocktails. To date, metagenomic analyses have also resulted in the identification of numerous potential lignocellulolytic enzymes [ 233 , 249 , 380 , 382 , 383 , 384 , 385 , 386 ]. Shotgun analysis of a bacterial consortium enriched with carboxymethylcellulose, for example, resulted in the reconstruction of six complete genomes, four of which were new, including Bacillus thermozeamaize , Geobacillus thermoglucosidasiu , and Caldibacillus debillis .…”
Section: Recent Advancesmentioning
confidence: 99%
“…Glucose and xylose are the main carbohydrates that can be obtained after pretreatment of residual lignocellulosic raw materials. The choice of the pretreatment method greatly influences the concentration of the aforementioned fermentable sugars (Mar detko et al, 2018(Mar detko et al, , 2021. Bacterium P. polymyxa can use glucose and xylose for its metabolic needs (Okonkwo et al, 2021).…”
Section: Growth Kinetics and Biochemicals Production During Cultivati...mentioning
confidence: 99%